Usefulness of parental response to questions about adherence to prescribed inhaled corticosteroids in young children - Schultz, A.; Sly, P.; Zhang, Guicheng; Venter, A.; Devadason, S.; Le Souëf, P. (2012)
Background: Adherence to prescribed inhaled medication is often low in young children. Poor adherence to medication may contribute to lack of symptom control. Doctors are not good at predicting the adherence rates of their patients, and parental report of adherence does not correlate with objective measures of adherence. The objective of this study was to investigate whether parental admission of non-adherence and reasons given for non-adherence correlated with objectively measured adherence. Methods: Adherence to prescribed inhaled corticosteroid treatment was monitored electronically in 132 children aged 2-6 years who were participating in a randomised controlled trial comparing different inhaler devices. Follow-up was carried out every 3 months for a year. Parental answers to simple questions about adherence were compared to electronically measured adherence. Results: Mean adherence ranged from zero to 100%. Intraparticipant adherence varied throughout the year-long study period (mean variance for individual children between quarterly periods was 28.5%). Parents who reported missed doses, generally missed at least half of the prescribed doses. Parents who reported that not a single prescribed dose was missed, still missed 20% of doses on average. Adherence was particularly low when parents cited initiating their own trial off medication as a reason for missing doses. Conclusions: By examining parental response to questions enquiring whether any doses were missed, healthcare providers can gain a modest degree of insight into their patients' true adherence to prescribed medication. Adherence to prescribed asthma medication is extremely variable in young children. Trial registration number: Data from this study were derived from a randomised controlled trial (ACTRN12608000294358).